2012
DOI: 10.1038/cmi.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Peli: a family of signal-responsive E3 ubiquitin ligases mediating TLR signaling and T-cell tolerance

Abstract: E3 ubiquitin ligases play a crucial role in regulating immune receptor signaling and modulating immune homeostasis and activation. One emerging family of such E3s is the Pelle-interacting (Peli) proteins, characterized by the presence of a cryptic forkhead-associated domain involved in substrate binding and an atypical RING domain mediating formation of both lysine (K) 63-and K48-linked polyubiquitin chains. A well-recognized function of Peli family members is participation in the signal transduction mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 100 publications
0
54
0
Order By: Relevance
“…We next used an LPS-induced septic-shock model to further investigate the in vivo function of TRIM29 in acute lung inflammation. In this acute model, death occurs within hours, mainly due to the production of TNF 30,31 . Age-matched wild-type and Trim29 −/− littermates were inoculated intranasally with LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next used an LPS-induced septic-shock model to further investigate the in vivo function of TRIM29 in acute lung inflammation. In this acute model, death occurs within hours, mainly due to the production of TNF 30,31 . Age-matched wild-type and Trim29 −/− littermates were inoculated intranasally with LPS.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that both the RING domain and the B-box domain of TRIM18 have E3 ligase activity, although the B-box domain exhibits weaker E3 ligase activity than that of a typical RING domain 29 . Furthermore, the E3 ligase Peli1 does not contain a typical RING domain, which suggests that not all E3 ligases use a typical RING domain to catalyze ubiquitination 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the disease-coding variant is located in the RING domain, a domain with a predicted E3 ubiquitin-protein ligase activity. Ubiquitin ligases have been shown to regulate key adaptors of proinflammatory pathways [15][17]. We previously reported that RNF186 expression was higher in human intestinal tissues than in immune tissues [8].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models have shown that IRAK2 is critical in sustaining late phase inflammatory responses after TLR stimulation, leading to increased production of inflammatory cytokines [21]. These molecules may also be important in T cell related functions, such as T cell tolerance [22], and promotion of Th17 cell development [23]. …”
Section: Discussionmentioning
confidence: 99%